Vertical distribution of metabolically active eukaryotes in the water column and sediments of the Black Sea - Coolen, Marco; Shtereva, G. (Oxford University Press, 2009)
Recent DNA-based phylogenetic studies have reported high eukaryotal diversities in a wide range of settings including samples obtained from anoxic environments. However, parallel RNA-based surveys are required in order to verify whether the species detected are in fact metabolically active in such extreme environments. The Black Sea is the World's largest anoxic basin but remains undersampled with respect to molecular eukaryotic diversity studies. Here, we report the distribution of active eukaryotes (18S rRNA-based survey) along a vertical nutrient and redox gradient in the water column and surface sediments of the Black Sea. A wide variety of eukaryotes were active in suboxic deep waters. Notably, certain species were active but escaped detection during a parallel 18S rDNA survey. The 18S rDNA survey from surface sediments yielded taxa of pelagic origin but none of these were identified from the water column at the time of sampling. Our data also indicate that gene transcripts do not always provide unequivocal proof that active microorganisms are indigenous to a specific position in an environmental gradient, because certain zoo- and phytoplankton species were still viable with detectable 18S rRNA in up to 300-year-old sulfidic sediments that underlie ~830 m of sulfidic waters. © 2009 Federation of European Microbiological Societies. Published by Blackwell Publishing Ltd. All rights reserved.